Conjunctivitis in the practice of a primary care physician – friend or foe? - Wilk, Jan; Jarmołowicz, Jakub; Krochmal, Karolina; Krzeszowska, Paulina; Kujawa, Aleksandra; Kuźma, Radosław; Marrodán-Wojtczak, Karolina; Samoraj, Adrianna; Stępniak, Kacper; Zajączkowski, Jakub (Journal of Education, Health and Sport, 2025)
Introduction and purpose: Conjunctivitis is one of the most common ocular conditions that primary care physicians encounter. As a very frequent and usually benign disease, most cases do not require a referral to a specialist and are managed by the general practitioners. Apart from being a stand-alone condition, conjunctivitis may also be a part of clinical presentations of some systemic diseases – both infectious and inflammatory. By being well-recognizable by GPs it can serve as an indicator, pointing them towards possible diagnoses and indicating the need for further testing. On the other hand, numerous ocular conditions share similar symptoms with conjunctivitis, some of which may be vision-threatening. It is therefore crucial not to misdiagnose them as simple or benign conjunctivitis, because overlooking and neglecting these diseases may have serious health consequences, including vision loss. The aim of this article is to review the condition, drawing attention to these two aspects of conjunctivitis as particularly important in the work of a primary care physician – as both a possible indicator for other, systemic conditions, and a diagnostic challenge due to a symptom overlap with many more severe ophthalmic diseases. Materials and methods: A review of literature was carried out using online platforms Google Scholar and PubMed. Articles were searched by entering keywords: conjunctivitis, red eye, primary care, general practice. Description of current knowledge: Conjunctivitis is a common condition often seen by general practitioners. It has three main types: viral, bacterial and allergic. It can manifest as a symptom of systemic diseases and shares symptoms with other eye conditions. Conjunctivitis is generally self-limiting and doesn’t require treatment. However, evident bacterial cases may benefit from antiseptic or antibiotic therapy to prevent complications and reduce transmission.